Preference-based versus randomized controlled trial in prostate cancer survivors: Comparison of recruitment, adherence, attrition, and clinical outcomes - Alibhai, Shabbir M. H.; Papadopoulos, Efthymios; Durbano, Sara; Tomlinson, George; Mina, Daniel Santa; Ritvo, Paul; Sabiston, Catherine M.; Matthew, Andrew G.; Chiarotto, James; Sidani, Souraya; Culos-Reed, S. Nicole (Frontiers in Oncology, 2022)
Introduction: Patients’ unwillingness to be randomized to a mode of exercise may partly explain their poor recruitment, adherence, and attrition in randomized controlled trials (RCTs) of exercise in oncology. It is unknown whether a preference-based trial can improve recruitment, adherence, retention, and clinical outcomes compared to a RCT of the same exercise interventions. Objective: We assessed the effects of a 2-arm exercise preference trial on adherence and clinical outcomes compared to a similar 2-arm RCT in men with prostate cancer (PC). Methods: This was a two-arm preference-based trial of group-based training (GROUP) or home-based training (HOME). PC survivors on androgen deprivation therapy (ADT) who declined randomization to the RCT but chose to participate in a preference trial were recruited in four Canadian centres. All study participants engaged in aerobic and resistance training, 4-5 days weekly for 6 months, aiming for 150 minutes/week of moderate-to-vigorous physical activity. The primary outcomes were changes from baseline to 6 months in fatigue and functional endurance. Secondary outcomes were quality of life, physical fitness, body composition, blood markers, and adherence. Linear mixed models were used to assess the effects of HOME versus GROUP on primary outcomes. In pooled preference and RCT data, the selection effect (i.e., difference between those who were and were not willing to be randomized) and treatment effect (i.e., difference between GROUP and HOME) were estimated using linear regression. Trial Registration: NCT03335631 Results & Conclusion: Fifty-four participants (mean [SD] age, 70.2 [8.6] years) were enrolled (GROUP n=17; HOME n=37). Comparable effects on primary and secondary outcomes were observed following GROUP or HOME in the preference-based trial. Adherence was similar between preference and RCT participants. However, attrition was higher in the RCT (50.0% vs. 27.8%, p= 0.04). Compared to GROUP, HOME was more effective in ameliorating fatigue (mean difference: +5.2, 95%CI=1.3 to 9.3 p=0.01) in pooled preference and RCT data. A preference-based trial results in comparable observed effects on clinical outcomes and adherence and lower attrition compared with a RCT of the same exercise interventions in PC survivors on ADT. Given the appeals of preference-based trials to study participants, additional studies are warranted.